2007
DOI: 10.1016/j.ab.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

A continuous fluorometric assay for the assessment of MazF ribonuclease activity

Abstract: Plasmids maintain themselves in their bacterial host through several different mechanisms, one of which involves the synthesis of plasmid-encoded toxin and antitoxin proteins. When the plasmid is present the antitoxin binds to and neutralizes the toxin. If a plasmid-free daughter cell arises, however, the labile antitoxin is degraded (and not replenished) and the toxin kills the cell from within. These toxin-antitoxin (TA) systems thereby function as post-segregational killing systems, and the disruption of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 34 publications
(72 reference statements)
0
43
0
Order By: Relevance
“…Considerable evidence has shown that TA modules in bacteria act as suicide systems in response to environmental stimuli such as nutritional deficiency, and protect bacteria from phage infection [39,51,56,57]. Interestingly, bacterial TA modules may be involved in the action against antibacterial agents in S. aureus and vancomycin-resistant enterococci [28,58]. However, several studies have revealed that the toxic proteins from prokaryotic TA modules cause the death of eukaryotic and mammalian host cells [38,59,60], suggesting the possibility that the TA modules in bacterial pathogens to play roles during host infection.…”
Section: Discussionmentioning
confidence: 98%
“…Considerable evidence has shown that TA modules in bacteria act as suicide systems in response to environmental stimuli such as nutritional deficiency, and protect bacteria from phage infection [39,51,56,57]. Interestingly, bacterial TA modules may be involved in the action against antibacterial agents in S. aureus and vancomycin-resistant enterococci [28,58]. However, several studies have revealed that the toxic proteins from prokaryotic TA modules cause the death of eukaryotic and mammalian host cells [38,59,60], suggesting the possibility that the TA modules in bacterial pathogens to play roles during host infection.…”
Section: Discussionmentioning
confidence: 98%
“…This was used as a substrate for WT and E24A MazF. RNase inhibitor was added to a final concentration of 1 unit/l to inactivate RNase A (32). MazF (0.01 or 0.05 g) was incubated with 6 g of RNA in PBS buffer, pH 7.4, at 37°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorogenic substrates have previously been used to analyze the reaction kinetics of ribonucleases (Park et al 2001;Wang and Hergenrother 2007) and generally consist of single RNA bases flanked by short DNA sequences. These mixed oligonucleotides are labeled with a fluorophore at one end and a quencher at the other.…”
Section: Kinetic Analysis Of Vapcmentioning
confidence: 99%
“…Once the specificity of VapC was known, detailed kinetic analyses were carried out using a sensitive fluorometric substrate similar to that of the method described by Kelemen et al (1999) and Wang and Hergenrother (2007) for quantitation of VapC activity and kinetic analyses of these enzymes.…”
Section: Introductionmentioning
confidence: 99%